Business as usual: A consumer search theory of sticky prices and asymmetric price adjustment - Luís Cabral; Arthur Fishman (Bar-Ilan University, Department of Economics, 2010)
Empirical evidence suggests that prices are sticky with respect to cost changes. Moreover, prices respond more rapidly to cost increases than to cost decreases. We develop a search theoretic model which is consistent with this evidence and allows for additional testable predictions. Our results are based on the assumption that buyers do not observe the sellers costs, but know that cost changes are positively correlated across sellers. In equilibrium, a change in price is likely to induce consumer search, which explains sticky prices. Moreover, the signal conveyed by a price decrease is different from the signal conveyed by a price increase, which explains asymmetry in price adjustment.
Keywords: 330; Preisrigidität; Anpassungskosten; Preismanagement; Konsumentenverhalten; Informationskosten; Suchtheorie